A novel feeder-free culture system for human pluripotent stem cell culture and induced pluripotent stem cell derivation. - Sanna Vuoristo; Sanna Toivonen; Jere Weltner; Milla Mikkola; Jarkko Ustinov; Ras Trokovic; Jaan Palgi; Riikka Lund; Timo Tuuri; Timo Otonkoski (PLoS ONE, 2013)
Correct interactions with extracellular matrix are essential to human pluripotent stem cells (hPSC) to maintain their pluripotent self-renewal capacity during in vitro culture. hPSCs secrete laminin 511/521, one of the most important functional basement membrane components, and they can be maintained on human laminin 511 and 521 in defined culture conditions. However, large-scale production of purified or recombinant laminin 511 and 521 is difficult and expensive. Here we have tested whether a commonly available human choriocarcinoma cell line, JAR, which produces high quantities of laminins, supports the growth of undifferentiated hPSCs. We were able to maintain several human pluripotent stem cell lines on decellularized matrix produced by JAR cells using a defined culture medium. The JAR matrix also supported targeted differentiation of the cells into neuronal and hepatic directions. Importantly, we were able to derive new human induced pluripotent stem cell (hiPSC) lines on JAR matrix and show that adhesion of the early hiPSC colonies to JAR matrix is more efficient than to matrigel. In summary, JAR matrix provides a cost-effective and easy-to-prepare alternative for human pluripotent stem cell culture and differentiation. In addition, this matrix is ideal for the efficient generation of new hiPSC lines.